Kepler as a statistician - Sheynin, Oscar (Silesian Statistical Review, 2017)
Drawing on my previous publications (see Bibliography), I describe Kepler’s work on the mathematical treatment of observations and astrology. In particular, I investigate how he rejected the Ptolemaic system of the world and note that his astrology had the features of qualitative correlation
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2017, Nr 15, s. 227-232
Keywords: reformation of astronomy; astrology; qualitative correlation; minimax method; Monte Carlo methods; reforma astronomii; astrologia; korelacja cech jakościowych; metoda Monte Carlo